1990
DOI: 10.1002/tera.1420410103
|View full text |Cite
|
Sign up to set email alerts
|

Unique anomalies in cephalothoracopagus Janiceps conjoined twins with implications for multiple mechanisms in the abnormal embryogenesis

Abstract: The anatomic features of female conjoined twins with the Janiceps type of cephalothoracopagus are described. Abnormalities included bilateral clefts of the alveolar arches, shared rudimentary mandible, high, arched clavicles, multiple rib deformities, single shared foregut and small intestine, absent large intestines, omphalocele, multicystic kidneys, hypoplastic lungs, interconnected aortas and neck vessels, single ovary with elongated uterus in each twin, displaced labia, abnormal segmentation of the vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In the case described by Sperber and Machin [9], there were separate larynges oriented to the vertebral axis, and the lungs and hearts were oriented to the faces. Baron and colleagues [10] reported a complex symmetric case of janiceps twinning with duplication and severe malformations caudally and reviewed 10 previously reported cases of janiceps cephalothoracopagus twins. All cases listed in this review had 2 hearts with variable defects, 4 lungs, some degree of gastrointestinal/hepatopancreatobiliary anomaly ranging from Meckel's diverticulum to intestinal/liver/pancreatic duplications, and duplication of central nervous system (CNS) structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the case described by Sperber and Machin [9], there were separate larynges oriented to the vertebral axis, and the lungs and hearts were oriented to the faces. Baron and colleagues [10] reported a complex symmetric case of janiceps twinning with duplication and severe malformations caudally and reviewed 10 previously reported cases of janiceps cephalothoracopagus twins. All cases listed in this review had 2 hearts with variable defects, 4 lungs, some degree of gastrointestinal/hepatopancreatobiliary anomaly ranging from Meckel's diverticulum to intestinal/liver/pancreatic duplications, and duplication of central nervous system (CNS) structures.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism is disorganization due to a low penetrance single gene defect, which would increase the risk of subsequent affected offspring [Petzel and Erickson, 1991]. CT are generally thought to develop from incomplete fission of a single zygote [Baron et al, 1990], although preimplantation embryonic fusion has also been suggested [Thompson et al, 1991]. In fact, mares have been shown to undergo asynchronous ovulations in which the initial implanted embryo acts as an impediment to the movement of the other, resulting in fixation of both embryos in the same uterine location [Ginther, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that each face in the janiceps type is made up of the right side of one twin and the left side of the other [Guttmacher and Nichols, 1967]. The degree of conjunction and deformity depends on the extent of fusion of the trunks [Wedberg et al, 1979; Delprado and Baird, 1984; Merwin and Wright, 1984; Baron et al, 1990]. The thoracic and abdominal organs are often duplicated.…”
Section: Clinical Reportsmentioning
confidence: 99%